Challenges in Job Seeking and the Integration of Ukrainian War Refugee Healthcare Workers Into the Polish Healthcare System: Facebook Content Analysis - Joanna Gotlib; Ilona Cieślak; Dominik Wawrzuta; Mariusz Jaworski; Dimitris Theofanidis; Grażyna Wójcik; Piotr Małkowski; Mariusz Panczyk (Frontiers Media S.A., 2023)
Objectives: The full-scale Russian invasion of Ukraine resulted in a refugee crisis. The terms of employment of Ukrainian Refugee background Medical Professionals (UKR-MPs) in the Polish healthcare system were liberalised. The aim of the study was to identify challenges in job seeking and the integration of Ukrainian war refugee healthcare workers into the Polish healthcare system.Methods: A qualitative, descriptive study based on content thematic analysis of Facebook content. We analyzed 1,700 posts published on two public Facebook groups intended for UKR-MPs.Results: The most common problems encountered by UKR-MPs were: 1) lack of easy-to-understand information about the list of documents necessary to apply for a work permit, 2) lack of feedback from those responsible for handling individual cases, and 3) long waiting time for the decision issued by the Ministry of Health.Conclusion: Despite the promptly implemented solutions enabling access to the job market by UKR-MPs, the refugees have encountered considerable administrative difficulties, as well as those arising from insufficient knowledge of the regulations on working as medical professionals in Poland under the EU law.